Factors That Influence Accounting Students' Interest in A Career as A Public Accountant - Amalia, Nabila; Bakhtiar, M. Rifki (Journal of Economics and Business UBS, 2024)
This research aims to analyze the factors that influence accounting students' interest in a career as a public accountant. The research data is primary data with data collection using a questionnaire with purposive sampling method. The results showed that academic ability, labour market considerations, and financial rewards had a positive and significant effect on accounting students' interest in a career as a public accountant. Professional training, work environment, and professional recognition have no effect on accounting students' interest in a career as a public accountant. This research provides evidence of which factors influence accounting students' interest in a career as a public accountant.